The Existence of The Application of Corporate Crime Against Limited Liability Companies in Cases of Environmental Pollution Due to The Impact of Factory Waste - Enus Ginting; Yasmirah Mandasari Saragih; Ahbym Faizan; Eddy Eddy; Eri Siswanto (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Environmental pollution due to factory waste is a crucial issue in Indonesia, especially regarding corporate responsibility. Law No. 32 of 2009 on Environmental Protection and Management and Law No. 40 of 2007 on Limited Liability Companies regulate the application of corporate criminal offenses against polluting companies. However, its application is often constrained, both in terms of proving corporate guilt and applying effective sanctions. This research aims to examine the application of criminal law against PTs in cases of factory waste pollution and challenges in law enforcement. The method used is descriptive qualitative with case study analysis. The results show that although regulations already exist, the application of sanctions against corporations is still not effective in providing a deterrent effect on the perpetrators of pollution.